Transformation sequence of Mg-Si precipitates towards a precipitation of Mn and Cr containing phase governed by the high strain-rate collision during magnetic pulse welding of Al-Mg-Si alloy - R.N. Raoelison; T. Sapanathan; J.S. Li; Z. Zhang; D. Racine; X.-G. Chen; D. Marceau; M. Rachik (Journal of Alloys and Metallurgical Systems, 2023)
This paper investigates the transformation of Mg-Si precipitates formed at an interface of an Al-Mg-Si alloy joint, welded by the high strain-rate collision during magnetic pulse impact welding. The Transmission Electron Microscopy (TEM) and Energy dispersive X-Ray (EDX) analysis of the precipitates reveal a nucleation of circular shape AlFeMnSiCr precipitate (size of ∼100 nm) from the dissolution of the native β″ (needle-shaped) precipitate. The AlFeMnSiCr phase can also reach a size up to several microns and grows into diverse shapes (rod-shaped, polygonal-shaped, ovoid-shaped). Based on the microstructural characterizations and on observations available in the literature including relevant data of Lodgaard and Ryum, the transformation sequence due to the high-speed collision can be described as follows: β″-Mg-Si (needle-shaped) → β’-Mg2Si (rod-shaped) ‘u-phase’ → Al(MnCrFe)Si (round-shaped) → Al(MnCrFe)Si +(+: Cr; Cu and/or Ni, rod-shaped, polygonal-shaped, ovoid-shaped). The comparison of samples welded at three different impact conditions (low impact intensity, intermediate impact intensity, high impact intensity) shows that the area fraction of the precipitates decreases with the increase of the impact intensity. The identification of the crystal structure of these different precipitates, from the nucleation to the final complete formation of the precipitation, can further enrich the transformation sequence in this paper. The role of the high strain kinematics on the deformation of the Al lattice and on the diffusion rate of alloying elements is also a perspective that can further explain this new observation of precipitation during magnetic pulse welding.